The possibility of leptonic CP-violation measurement with JUNO - M.V. Smirnov (Nuclear Physics B, 2018)
The existence of CP-violation in the leptonic sector is one of the most important issues for modern science. Neutrino physics is a key to the solution of this problem. JUNO (under construction) is the near future of neutrino physics. However CP-violation is not a priority for the current scientific program. We estimate the capability of δCP measurement, assuming a combination of the JUNO detector and a superconductive cyclotron as the antineutrino source. This method of measuring CP-violation is an alternative to conventional beam experiments. A significance level of 3σ can be reached for 22% of the δCP range. The accuracy of measurement lies between 8o and 22o. It is shown that the dominant influence on the result is the uncertainty in the mixing angle Θ23.